2011
DOI: 10.1159/000329901
|View full text |Cite
|
Sign up to set email alerts
|

<i>Candida albicans</i>-Induced Chronic Thrombocytopenic Purpura

Abstract: We present 2 patients with chronic immune thrombocytopenic purpura (ITP) secondary to Candida albicans infection. Neither patient responded to standard ITP therapy including splenectomy. Appropriate antifungal treatment of the C. albicans infection was followed by sustained improvement in platelet count in both patients. To our knowledge, this is the first report of ITP in association with C. albicans infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A study on dengue fever with cobalamin deficiency showed significant improvement in hematological parameters including thrombocytopenia after administering vitamin B12 to the patients [ 15 ]. Ayesh and Alawneh have reported two incidents of chronic ITP in cases of vulvovaginal candidiasis in contrast to our case which had oesophageal candidiasis and acute ITP [ 16 ]. An article on Candida and platelet interaction has shown that Candida -derived secretory products did not affect platelet activity neither stimulatory nor inhibitory [ 17 ].…”
Section: Discussioncontrasting
confidence: 59%
“…A study on dengue fever with cobalamin deficiency showed significant improvement in hematological parameters including thrombocytopenia after administering vitamin B12 to the patients [ 15 ]. Ayesh and Alawneh have reported two incidents of chronic ITP in cases of vulvovaginal candidiasis in contrast to our case which had oesophageal candidiasis and acute ITP [ 16 ]. An article on Candida and platelet interaction has shown that Candida -derived secretory products did not affect platelet activity neither stimulatory nor inhibitory [ 17 ].…”
Section: Discussioncontrasting
confidence: 59%
“…This may be the reason why the relative risk was more noticeable for diagnosis than for prescribed fungal drugs. A case report study of Candida albicans reported two patients who developed refractory chronic ITP, possibly due to an underlying Candida infection . The authors reported improvement in platelet count in both patients after proper treatment and eradication of Candida albicans infection.…”
Section: Discussionmentioning
confidence: 94%
“…All the patients who were treated with rifampicin (600 mg daily) and doxycycline (200 mg daily) restored their normal blood platelet counts after one month of treatment, while tube agglutination tests for brucellosis became progressively negative. 51 Nonetheless, Ayesh Haj Yousef and Alawneh 52 recently observed two cases of Candida albicans -induced chronic thrombocytopaenic purpura. One was a 39-year-old woman with type 1, insulin-dependent diabetes mellitus who developed severe thrombocytopaenia (10 3 platelets/µl) with megakaryocytic hyperplasia.…”
Section: Non-viral Infectionsmentioning
confidence: 99%
“…The second case of C. albicans -associated severe ITP was also well controlled by antifungal therapy in a 43-year-old woman who failed to achieve remission after the multistep treatment as reported above, until consistent anti-yeast therapy was administered and resulted in effective and safe in every platelet drop relapse. 52…”
Section: Non-viral Infectionsmentioning
confidence: 99%